2018
DOI: 10.1016/j.jenvman.2017.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Modelling hydrodynamics of horizontal flow steel slag filters designed to upgrade phosphorus removal in small wastewater treatment plants

Abstract: Steel slag filters, if well designed and operated, may upgrade phosphorus removal in small wastewater treatment plants such as stabilization ponds and constructed wetlands. The main objective of this study was to develop a systemic modelling approach to describe changes in the hydraulic performances and internal hydrodynamics of steel slag filters under real dynamic operating conditions. The experimental retention time distribution curves (RTD curves) determined from tracer experiments performed at different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…However, the lower particle size can also result in lower pore size between the grains, thus reducing the hydraulic conductivity of the filters [35]. In addition, various biological and physical-chemical phenomena, including biofilm growth, retention of suspended solids, particle segregation, precipitation and accumulation of precipitates, may further decrease the void volume and the pore size [36], thus affecting the long-term hydraulic and treatment performances of the filters and increasing the risk of clogging when treating real effluents. Therefore, Herron et al [34] recommended the < 6 mm as optimum particle-size in field scale applications.…”
Section: P Removal Performancesmentioning
confidence: 99%
“…However, the lower particle size can also result in lower pore size between the grains, thus reducing the hydraulic conductivity of the filters [35]. In addition, various biological and physical-chemical phenomena, including biofilm growth, retention of suspended solids, particle segregation, precipitation and accumulation of precipitates, may further decrease the void volume and the pore size [36], thus affecting the long-term hydraulic and treatment performances of the filters and increasing the risk of clogging when treating real effluents. Therefore, Herron et al [34] recommended the < 6 mm as optimum particle-size in field scale applications.…”
Section: P Removal Performancesmentioning
confidence: 99%
“…Advantages inherent to these models include first, the possible calculation of the loss of effective porosity at each iteration of the simulation based on the mass precipitated. The TIS model, however, does not offer a mechanistic approach to calculate the evolution of hydraulic parameters, even if it was successfully used to calibrate tracer tests of full-scale AGFs [13]. Indeed, there is no direct mathematical relationship between the TIS hydraulic parameters (N, HRT Ve ) and the porosity reduction caused by the volume occupied by precipitates.…”
Section: Implications For Alkaline Granular Filters Hydraulic Modelsmentioning
confidence: 99%
“…The large amount production of iron-and steelmaking slag has proposed a great challenge to the environment as it has been considered as pollutant. In fact, the slag has showed impressive performance on removing contaminants from air, water, and soil (Barca et al 2014(Barca et al , 2018Jo et al 2015;Yu et al 2015;Zhou et al 2016;Zuo et al 2015). It indicates that the iron-and steelmaking slag has great potential in the application of environment treatment practice.…”
Section: Application In Environmental Treatmentsmentioning
confidence: 99%
“…Studies using iron-and steelmaking slag as filtration media have shown that the slag had good performance in various types of wastewater treatment and revealed that the slag was capable of removing contaminants such as suspended solids, chemical oxygen demand (COD), biochemical oxygen demand (BOD), phosphate (P), and ammonium (N-NH 4 ? ) ( Barca et al 2014Barca et al , 2018Kadirova et al 2015;Zhou et al 2016;Zuo et al 2015). It was predicted that the porous structure of the slag would absorb the contaminants and free lime in the slag could react with the contaminants (Jha et al 2004(Jha et al , 2008Lu et al 2008).…”
Section: Water Treatmentmentioning
confidence: 99%
See 1 more Smart Citation